Nuclear Magnetic Resonance Spectroscopy. A Stereospecific (3)J(CF) Coupling in the Low-Temperature (13)C Nmr Spectrum of 1,1-Difluorocyclohexane - Doddrell, David (1970)
The proton-decoupled (13)C nmr spectrum of 1,1-difluorocyclohexane has been examined at room temperature and at -90°C. There are only minor changes in the one-bond and two-bond carbon-fluorine scalar coupling constants at the lower temperature; however, the triplet observed for C-3 ((3)J(CF) = 4.7 Hz) collapses to a doublet ((3)J(CF) = 9.5 Hz) at -90°C. It is proposed that only the equatorial fluorine is coupled with the C-3 carbon as the result of operation of a back-lobe orbital interaction.